Former Very Preterm Infants Show Alterations in Thyroid Function at a Preschool Age. (19th July 2017) - Posod, Anna; Odri Komazec, Irena; Pupp Peglow, Ulrike; Meraner, Dagmar; Griesmaier, Elke; Kiechl-Kohlendorfer, Ursula
Abstract : Preterm birth is frequently associated with altered thyroid hormone levels in the newborn period. Recent data suggest a role of prematurity independent of birth size also in childhood thyroid dysfunction. Whether the high-risk population of former very preterm infants (VPI) is particularly susceptible to thyroid hormone alterations is currently unknown. The aim of the present study was to assess whether former VPI display changes in thyroid hormone status in comparison to term-born controls at a preschool age. Free triiodothyronine (fT3), free thyroxine (fT4), and thyroid stimulating hormone (TSH) concentrations were determined in former VPI and same-aged children born at term at five to seven years of age. 31 former term infants and 82 former VPI were included in the study. In comparison to children born at term, former VPI had lower fT4 (16.1 ± 1.8 versus 17.0 ± 2.1  pmol/l), higher fT3 (6.8 ± 0.7 versus 6.5 pmol/l), and higher TSH levels (3.0 ± 1.4 versus 2.3 ± 1.0   μ U/l), independent of major neonatal morbidities. As subclinical changes in thyroid hormone status are potentially associated with adverse health profiles, close follow-up of these children is warranted.